Manajemen Sarana dan Prasarana Pendidikan Dalam Peningkatan Efektifitas Pembelajaran Mahasiswa - Poltak Sihar Nainggolan; Robinhot Sihombing; Senida Harefa (International Forum of Researchers and Lecturers, 2024)
This research was conducted to examine/find out whether there is management of facilities and infrastructure in achieving learning effectiveness and to find out how the management of facilities and infrastructure is carried out at STT Baptist Medan. This type of research is qualitative. Data collection from informants was obtained through observation, interviews and documentation. The qualitative data obtained will be analyzed through the stages of data collection, data reduction, data display, and drawing conclusions/verification. The results of the research show that the management of facilities and infrastructure in achieving learning effectiveness at STT Baptist Medan includes the following: analyzing the needs and planning of educational facilities and infrastructure, procurement, inventory, utilization, maintenance, removal and supervision. Through the management of educational facilities and infrastructure carried out at STT Baptist Medan in accordance with theory and in the field, learning effectiveness can be increased, because when facilities and infrastructure are used effectively and efficiently they can contribute to education, namely: facilitating the learning and teaching process. When students and lecturers experience ease in accessing information and learning, the abilities of students and lecturers can increase so that interactions during learning can take place effectively and efficiently.